APLICAÇÃO DE NANOPARTÍCULAS MAGNÉTICAS COMO MEIO DE CONTRASTE EM MEDICINA NUCLEAR E TOMOGRAFIA COMPUTADORIZADA - Dias, Argleydson Leão (2009)
The research developed in recent years shows the high potential of use of ferrofluids in biomedical applications. One major area, in particular, is the use of biocompatible magnetic nanoparticles as contrast agents in the cancer diagnostic and treatment. In this work we evaluate the application of a fluid composed by magnetic nanoparticles of magnetite stabilized by coating with dimercaptosuccinic acid (DMSA-FM) in an aqueous medium as a contrast agent in nuclear medicine and computed tomography. The application in nuclear medicine were carried out firstly performing radiochemical studies and second by performing in vivo images of rats. The radiochemical studies shows that about 31% of technetium remained in the free form, not bounded totaly to the FM - DMSA, and so comprometing the location of the compound in several organs of the animal. The application of nanoparticles in computed tomography was performed by using a head simulator object where syringes containing different amounts of FM-DMSA and iodine, diluted in water were attached in order to compare the contrast produced in the image by these two compounds. The results showed that the attenuation by the FM-DMSA is approximately five times lower than the values produced by the iodine. Although the attenuation produced by the compound FMDMSA is less than that produced by iodine, the compound shows favorable properties for applications as a contrast agent in computed tomography, since its effective atomic number is much larger than those of soft tissues and the HU values measured at the images are in the range of those produced by bone tissues.